Comprehensive survey of transposon mPing insertion sites and transcriptome analysis for identifying candidate genes controlling high protein content of rice - Monden, Yuki; Tanaka, Hirona; Funakoshi, Ryota; Sunayama, Seiya; Yabe, Kiyotaka; Kimoto, Eri; Matsumiya, Kentaro; Yoshikawa, Takanori (Frontiers in Plant Science, 2022)
Rice is the most important crop species in the world, being staple food of more than 80% of people in Asia. About 80% of rice grain is composed of carbohydrates (starch), with its protein content as low as 7%–8%. Therefore, increasing the protein content of rice offers way to create a stable protein source that contributes to improving malnutrition and health problems worldwide. We detected two rice lines harboring a significantly higher protein content (namely, HP5-7 and HP7-5) in the EG4 population. The EG4 strain of rice is a unique material in that the transposon mPing has high transpositional activity and high copy numbers under natural conditions. Other research indicated that mPing is abundant in the gene-rich euchromatic regions, suggesting that mPing amplification should create new allelic variants, novel regulatory networks, and phenotypic changes in the EG4 population. Here, we aimed to identify the candidate genes and/or mPing insertion sites causing high protein content by comprehensively identifying the mPing insertion sites and carrying out an RNA-seq-based transcriptome analysis. By utilizing next generation sequencing (NGS)-based methods, ca. 570 mPing insertion sites were identified per line in the EG4 population. Our results also indicated that mPing apparently has a preference for inserting itself in the region near a gene, with 38 genes in total found to contain the mPing insertion in the HP lines, of which 21 and 17 genes were specific to HP5-7 and HP7-5, respectively. Transcriptome analysis revealed that most of the genes related to protein synthesis (encoding glutelin, prolamin, and globulin) were up-regulated in HP lines relative to the control line. Interestingly, the differentially expressed gene (DEG) analysis revealed that the expression levels of many genes related to photosynthesis decreased in both HP lines; this suggests the amount of starch may have decreased, indirectly contributing to the increased protein content. The high protein lines studied here are expected to contribute to the development of high protein-content rice by introducing valuable phenotypic traits such as high and stable yield, disease resistance, and abundant nutrients.